A kényszerkollektivizálás következményei az egyházközségek gazdasági életére és infrastruktúrájára Szolnok megyében, 1959-1962 - Sulák Péter Sándor (Középkori és Kora Újkori Magyar Történeti Tanszék Szeged, 2023)
The present study examines the ecclesiastical-historical aspects of the forced collectivisation of agriculture through the example of Szolnok County, which was a sample area of the Great Hungarian Plain. The ecclesiological consequences of the full-scale implementation of collectivization between 1959 and 1962 were of particular importance for the Hungarian Socialist Workers’ Party. In addition to the documents of the Presidential and downgraded Secretly Administered State Office of Church Affairs, the research relies on the documents produced by the lower administrative level council and party bodies of the local and regional level of the party state established after Sovietization. The project focuses on the everyday pressures of power exercised by the local organs of the party state and aims to explore the effects on the economic situation of the congregations, traditional community behaviours and micro-social structures in the mixed-denominational landscape of Jászság and Nagykunság. Relatively little is known about the economic, social, and cultural effects of forced collectivisation on historical denominations. An authentic image of this can be found in a micro-level study of a well-defined area, in an authentic depiction of the local clergy’s environment of action, its relations with the party-state organs and its own congregation. This is the aim of the study, which is intended to provide a basis for further research.
Keywords: Bölcsészettudományok; Történettudomány és régészet